Corporate Social Responsibility Through the Berkah Mulya Waste Bank Program - Sehan Yudha Fahreza; Dicky Triansyah; Siti Khumayah; Aghnia Dian Lestari (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the implementation of the Berkah Mulya Waste Bank program as a Corporate Social Responsibility (CSR) initiative of PT. Japfa Comfeed Cirebon. In waste management and community empowerment. This study employs a descriptive qualitative method, utilizing observation, in-depth interviews, and documentary analysis as data collection techniques. It also explores the workflow of the waste bank and its impacts based on the Triple Bottom Line concept (Profit, Planet, People). The research findings indicate that this program contributes positively economically through additional income for the community, environmentally through reduced waste volume and improved cleanliness, and socially through increased awareness, active participation, and community collaboration in waste management. However, the study also identified challenges in maintaining customer participation and a lack of succession planning for managers. Efforts to address these challenges include continuous education and the use of digital technology to attract the interest of younger generations. In conclusion, the Berkah Mulya Waste Bank is a successful CSR practice model that integrates environmental, social, and economic aspects and has the potential to be replicated as a community-based waste management solution in other regions.